Pengembangan Sistem Informasi Monitoring Praktek Kerja Lapangan Siswa di SMK Negeri 2 Padang berbasis Flutter Android dengan Implementasi REST API - Pranoto, Dzenata Achmad; Farell, Geovanne; Dewi, Ika Parma; Delianti, Vera Irma (Lembaga Yasin AlSys, 2025)
This study aims to develop a mobile-based information system for monitoring Praktek Kerja Lapangan (PKL) using Flutter Android, integrated with a REST API, at SMK Negeri 2 Padang. The research is motivated by the need to digitize the PKL monitoring process, which has traditionally been conducted manually, resulting in inefficiencies and lack of structure. The development method employed is the Waterfall model of the Software Development Life Cycle (SDLC), encompassing the stages of requirements analysis, system design, implementation, testing, and maintenance. The developed system features key functionalities such as online PKL information delivery, camera-based attendance validation (front and rear cameras), daily digital journal management, evaluation, and real-time data reporting. Testing results using the White Box method indicate that all logical paths function correctly, with Cyclomatic Complexity values within acceptable limits. The study concludes that the developed PKL monitoring information system meets both functional and technical requirements, and effectively supports the PKL monitoring process in an efficient, transparent, and structured manner. The findings underscore the importance of digitizing PKL supervision systems in vocational schools to enhance the effectiveness of work-based learning.